2018
DOI: 10.2514/1.j056504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nozzle–Plate Distance on Acoustic Phenomena from Supersonic Impinging Jet

Abstract: For an adequate understanding of the broadband acoustic phenomena generated by a rocket exhaust jet impinging on a flame deflector, this study experimentally clarifies the factors that cause the difference in the broadband acoustic field of a supersonic ideally expanded jet impinging on an inclined flat plate for various nozzle-plate distances. According to previous studies, there are two possible factors: the Mach waves, which are radiated from the free-jet region and reflected by the plate, and the acoustic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…III.A. A wall jet has similarly been observed for supersonic jets impinging on an inclined plate in the experiments of Akamine et al [39,40] for M j 1.8 and in the simulations of Nonomura et al [41,42] for M j 2. In these studies, Mach waves were found to be emitted by the wall jet, due to the supersonic convection velocity of the jet turbulent structures.…”
Section: B Mean Flowfieldsmentioning
confidence: 60%
“…III.A. A wall jet has similarly been observed for supersonic jets impinging on an inclined plate in the experiments of Akamine et al [39,40] for M j 1.8 and in the simulations of Nonomura et al [41,42] for M j 2. In these studies, Mach waves were found to be emitted by the wall jet, due to the supersonic convection velocity of the jet turbulent structures.…”
Section: B Mean Flowfieldsmentioning
confidence: 60%
“…Then, some investigations have been performed on impinging jets on an inclined flat plate [5]. Effects of nozzle-exit distance and tilt angle have been investigated [6]. Next step was to consider a horizontal flat plate [7] equipped with an exhaust hole [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The result evidenced that the impingement angle is a vital factor in the reduction of sound pressure near the rocket. In recent years, Akamine et al (2018) analysed the influence of different nozzle-plate distances on the expand jet impingement flow field. Their conclusions state that the separation distance had a considerable effect on the structure of the flow field, which was in turn generated in the free jet region and reflected by the deflector surface.…”
Section: Introductionmentioning
confidence: 99%